Resonant soft X-ray scattering for polymer materials. (August 2016) - Liu, Feng; Brady, Michael A.; Wang, Cheng
Graphical abstract: Highlights: Scattering using resonant soft X-rays probes nano- to meso-scale structures. Tunable contrast provides chemical sensitivity for complex structural information. Resonant polarized X-rays elucidate molecular orientation. In-Situ RSoXS probes morphology, chemistry and dynamics of broad range of materials. Abstract: Resonant Soft X-ray Scattering (RSoXS) was developed over the last a few years, and the first dedicated resonant soft X-ray scattering beamline for soft materials was constructed at the Advanced Light Source, LBNL. RSoXS combines soft X-ray spectroscopy with X-ray scattering and thus offers statistical information for 3D chemical morphology over a large length scale range from nanometers to micrometers. Using RSoXS to characterize multi-length scale soft materials with heterogeneous chemical structures, we have demonstrated that soft X-ray scattering is a unique complementary technique to conventional hard X-ray and neutron scattering. Its unique chemical sensitivity, large accessible size scale, molecular bond orientation sensitivity with polarized X-rays, and high coherence have shown great potential for chemically specific structural characterization for many classes of materials.